Genetic analysis of physiological traits to increase grain partitioning in high biomass cultivars in wheat (Triticum aestivum L.) - Sierra-Gonzalez, Aleyda (2020)
Wheat (Triticum spp.) is the second most grown crop in the world, being used as a raw ingredient in different foods making this cereal an essential component of the global food security. FAO estimates that for 2050, the global population could reach between 9.3 to 10 billion people (Peña-Bautista et al., 2017). The current global rate of yield increase in wheat is approximately 1% per year (FAOSTAT, 2013); however, to meet predicted future demand and avoid price hikes, taking into consideration unpredictable climate, genetic gains in grain yield potential are required of 1.5% per year (Fischer & Edmeades, 2010). To achieve this, it is essential to expand current understanding of how physiological traits are associated with genetic gains in yield potential and to adopt phenotypic and genotypic approaches to increase crop productivity (Aisawi et al., 2015).